HORIZONTAL AND VERTICALEQUITYASCRITERIA FORALLOCATIONFUNDFINANCIAL RESOURCESDEVELOPMENTNATIONALEDUCATIONPERUANA - Pacheco lay, Gonzalo (2014)
On two occasions (1966 and 1992) the level of public education spending per student from Peru, is found using the model designed by Mingat and Tan, that the source of resources constrains the advancement of education is economic. On the other hand, the dynamics followed by the enrollment realizes that expanding access was one of the objectives of relevant educational policy in recent decades. Under the horizontal and vertical equity concept proposed by Alejandro Morduchowicz, Peru has a way to go in education. There is no comparative experience in this dimension of reality, apparently, linking inequality with development The paper concludes by proposing three recommendations for education policy in its broadest possible sense: An education policy that seeks, in Peru, improve the quality of the results should recognize the existence of an economic nature ballasts, try searching both horizontal equity education vertical, anchored in the possibility of improving student performance, involves increasing resources to the sector, and the social contract that would look would translate into state policy.